Pengaruh Lingkungan Bisnis Terhadap Strategi Manufaktur: Studi Pada Perusahaan Manufaktur Di Kabupaten Bantul - Liestyana, Yuli; Gusaptono, R Hendri; Sufatmawati, Khirul Novia (208-7721)
The study analyzed the effect of business environment factors on manufacturing strategy. Data was collected from 43 organisations in Bantul, Yogyakarta. The analyses using Multivariate Multiple Regression Analysis (MMRA) found the results that simultaneously the factors of business environment effected manufacturing strategy. But, partially they did not. Only business cost, labor availability, and market dynamism significantly influenced manufacturing strategy.